2012
DOI: 10.1128/aem.07972-11
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Quantitative Environmental Surveillance in Poliovirus Eradication Strategies

Abstract: ABSTRACTThe progress of the Global Polio Eradication Initiative is monitored by acute flaccid paralysis (AFP) surveillance supplemented with environmental surveillance in selected areas. To assess the sensitivity of environmental surveillance, stools from (re)vaccinated elderly persons with a low seroprevalence and from wastewater were concurrently collected and analyzed in the Netherlands over a prolonged period of time. A total number of 228 healthy individuals with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 38 publications
5
49
0
Order By: Relevance
“…Since silent transmission of PV can be severe in our country, the number of infected persons (not ill) can exceed 1,000 before detection by AFP surveillance. We show that in our setup the detection of poliovirus by environmental surveillance will curtail the time to detection and the number of infected persons dramatically, as was suggested for OPV types 1 and 3 in the Dutch population (15) and for wild poliovirus type 1 spread in Israel (16). This clearly supports the aim of WHO for the expansion of environmental surveillance as a tool to strengthen polio surveillance during the endgame of poliovirus eradication (17).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Since silent transmission of PV can be severe in our country, the number of infected persons (not ill) can exceed 1,000 before detection by AFP surveillance. We show that in our setup the detection of poliovirus by environmental surveillance will curtail the time to detection and the number of infected persons dramatically, as was suggested for OPV types 1 and 3 in the Dutch population (15) and for wild poliovirus type 1 spread in Israel (16). This clearly supports the aim of WHO for the expansion of environmental surveillance as a tool to strengthen polio surveillance during the endgame of poliovirus eradication (17).…”
Section: Discussionsupporting
confidence: 80%
“…We detected only one PV1 SL in PRC-Ter Apel sewage samples. The PRC samples were collected 3 times per week, and considering the detection limit and population size at the PRC, we estimated detection of single shedders at the average level of shedding (2.3 ϫ 10 4 CCID 50 per g in a seronegative population [15]). Lower levels of shedding indeed result in reduced likelihood of detection and in reduced likelihood of continued transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hovi et al (5) reported that by analyzing a single 400-ml specimen, PV circulation could be detected if about 100 individuals were infected with PV in a population of 700,000 people. Lodder et al (14) found that it is possible to detect 100 PVinfected individuals in a population of tens of thousands uninfected individuals. In our situation, both the JNEW and LYSC plants treated 200,000 tons of sewage daily.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of ENVS is that it can detect PV circulation in the absence of clinical cases since virus is excreted into sewage during asymptomatic infections as well as symptomatic infections. Moreover, results can be semi quantitative as well as qualitative (Hovi et al, 2012;Hovi et al, 2001;Lodder et al, 2012;Manor et al, 2014).…”
Section: Poliomyelitis Vaccination and Eradication Updatementioning
confidence: 99%